Memorando el imperialismo: 1713, cuando Europa abandonó a los catalanes - Marfull Pujadas, Andreu (2019)
https://www.elpais.cr/2019/04/18/memorando-el-imperialismo-1713-cuando-europa-abandono-a-los-catalanes/